Quality of life and emotional distress in sarcoma patients diagnosed during COVID-19 pandemic: a supplementary analysis from the SarCorD study - Onesti, Concetta Elisa; Vari, Sabrina; Minghelli, Denise; Nardozza, Francesca; Rossi, Barbara; Sperati, Francesca; Checcucci, Elisa; Faltyn, Wioletta; Cercato, Maria Cecilia; Cosimati, Antonella; Salvatori, Francesca; Biagini, Roberto; et al. (Frontiers in Psychology, 2023)
Background The COVID-19 outbreak had a negative psychological impact on cancer patients. In this study, we analyzed emotional distress and quality of life in patients diagnosed with sarcoma during the first year of the pandemic compared to the previous year. Methods We retrospectively enrolled patients with soft tissue, bone sarcoma, and aggressive benign musculoskeletal diseases diagnosed during the pandemic (COVID group) or the year before (control group) at the IRCCS Regina Elena National Cancer Institute in Rome. Patients who had undergone a psychological assessment with the EORTC QLQ-C30 and the Distress Thermometer at diagnosis were included in the final analysis. We analyzed whether there is a difference in the various domains of quality of life between the two groups and whether there are changes over time in each group. Results We enrolled 114 patients (72 control group; 42 COVID group), affected by soft tissue (64%), bone sarcoma (29%), and aggressive benign musculoskeletal diseases (7%). We did not observe significant differences in the health-related quality of life domains in the control and COVID groups, except for the financial domain (p = 0.039), with 9.7% vs. 23.8% of patients with a score > 0 in the control and COVID groups, respectively. We observed emotional distress at diagnosis in 48.6% of patients in the control group vs. 69.0% in the COVID group (p = 0.034). In the control group, we observed an improvement in physical function (p = 0.043) and in QoL (p = 0.022), while in the COVID group, we observed a deterioration in role function (p = 0.044) during follow-up. In the COVID group, 22.2% of patients were concerned about COVID-19, 61.1% by tumor, 91.1% stated that the pandemic worsened their subjective perception of cancer, and 19.4% perceived that their quality of care had worsened. Conclusion We observed a higher level of distress among patients diagnosed during the pandemic compared to the year before, probably due to the increased concern for both infection and cancer, the worsened perception of health status, and the perception of a poorer quality of health care.